Penguatan Kepedulian Sosial Melalui Program Santunan Anak Yatim di Desa Singa Gembara Kutai Timur - Eko Nursalim (Ahsan: Jurnal Ilmiah Keislaman dan Kemasyarakatan, 2025)
Community service through orphan support programmes is a tangible implementation of the three pillars of higher education in contributing socially to communities in need. This study examines the implementation of the orphan support programme in Singa Gembara Village, East Kutai, which involves collaboration between educational institutions, village governments, community leaders, and local communities. The research method uses a participatory approach with data collection techniques through direct data collection, observation, and programme evaluation. The results show that the programme has successfully distributed assistance to 120 orphans with a positive impact on improving welfare, learning motivation, and strengthening social awareness in the community. Key factors for success include careful planning, active community participation, synergy between stakeholders, and a combination of material assistance and psychosocial support. Challenges that still need to be addressed include the integration of beneficiary data and infrastructure limitations in remote areas. Strategic recommendations include the development of a digital data collection system, strengthening the capacity of local communities, expanding the network of donors, and developing sustainable empowerment programmes to improve the long-term independence of orphans.